Writers and their readers: the phenomenon of collective sponsorship in Dalmatia in the first half of the 19th century (Libellarium: journal for research in the field of information and related sciences, 2011)
In most of the Western European countries the late 18th and the early 19th centuries were marked by significant changes in the field of book production, reading habits and reading culture in general. These changes resulted, among other things, in a growing number of readers and their significance. Although some changes in reading habits occurred in Dalmatia, albeit to a limited extent and with less influence on society as a whole, the reading public (though quite restricted in terms of its number) gained great significance in this region too, particularly in the early 19th century, marked by the growing national sentiment all around Europe. The importance of the reading public was the most evident in a more and more widespread model of collective sponsorship, which in the social history of book had not attracted the necessary attention among Croats. This new publishing and library phenomenon implied a system of subscription and gradually replaced a long-established model of individual funding. Based on the research on book production in all the three Dalmatian printing and publishing centres - Zadar, Split and Dubrovnik - in the period from 1815 till 1850 - the aim of this paper is to show that the phenomenon of collective sponsorship can be regarded as a new relationship between a writer and his/her readers, which gradually began to emerge. The author analyses the intensity of the system of subscription, reasons for its increasingly widespread use, as well as the ways and context of its practice. First, the paper discusses the problems which writers (as well as publishers and printers) faced while attempting to obtain financial support. Second, the paper shows the writers’ efforts to attract as many subscribers as possible, usually by constant appeals for subscription published in newspapers and journals of the period. Third, the paper suggests that finding subscribers became particularly important in the early 19th century, when many writers tended to support the national welfare by their nationally imbued writings, usually but not exclusively written in the vernacular. They cherished the idea of considering the collective sponsorship the greatest expression of patriotism, particularly from the late 1840s when both the appeals for subscription and books with accompanying subscription lists became more common. The paper also gives an insight into the authorship and character of the books with subscription lists as well as a general insight into the body of their subscribers. Finally, the paper concludes that in spite of the fact that one can hardly identify a motive for subscription for each subscriber (which can be done only by consulting a series of other sources), patriotism was definitely the most frequent one, in tune with the overall national spirit of the early 19th century.
Keywords: collective sponsorship; collective funding; subscription; writer; readers; Dalmatia; 19th century